2017
DOI: 10.2486/indhealth.2016-0083
|View full text |Cite
|
Sign up to set email alerts
|

Safety in ready mixed concrete industry: descriptive analysis of injuries and development of preventive measures

Abstract: Ready mixed concrete (RMC) industry, one of the barebones of construction sector, has its distinctive occupational safety and health (OSH) risks. Employees experience risks that emerge during the fabrication of concrete, as well as its delivery to the construction site. Statistics show that usage and demand of RMC have been increasing along with the number of producers and workers. Unfortunately, adequate OSH measures to meet this rapid growth are not in place even in top RMC producing countries, such as Turke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…However, the branches of industry in which repeated processes are dominant are being better chosen in order to obtain economical and effective outputs [40]. The most important advantage of this method is the fact that the method is not entirely based on personal assessments and the hazard analysis is performed simultaneously with the work itself [41,42].…”
Section: Job Safety Analysismentioning
confidence: 99%
“…However, the branches of industry in which repeated processes are dominant are being better chosen in order to obtain economical and effective outputs [40]. The most important advantage of this method is the fact that the method is not entirely based on personal assessments and the hazard analysis is performed simultaneously with the work itself [41,42].…”
Section: Job Safety Analysismentioning
confidence: 99%
“…We usually use Occupational Safety and Health (OSH) measures to prevent risky, unprecedented, and unpredictable situations [18,19]. We take two main approaches when dealing with an ergonomic intervention; one is the reactive approach, which looks at the ergonomics by considering the workstation (from work design perspective) after some physical disorder occurs or when musculoskeletal disorder has already occured [20,21].…”
Section: Ergonomic Factors and Musculoskeletal Disordersmentioning
confidence: 99%
“…However, current studies mostly focus on quality control [33][34], scheduling [35][36], waste management [37][38], delivery problems [39][40], and so on. Since safety and health is a rather new topic in RMC industry, statistical and academic studies are rarely found and limited [41]. Research studies on the subject are not abundant not only in Turkey but also in other countries.…”
Section: Introductionmentioning
confidence: 99%